Assessment of Spatiotemporal Gait Parameters in Patients with Lumbar Disc Herniation and Patients with Chronic Mechanical Low Back Pain - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2019)
AIM: To assess spatiotemporal gait parameters in patients with lumbar disc herniation (LDH) and chronic mechanical low back pain (CMLBP), and compare with healthy control group. MATERIAL and METHODS: A total of 70 patients was enrolled in this prospective, controlled cross-sectional study, of which 25 with LDH, 25 with CMLBP and 20 healthy individuals as the control group. Participants completed 10 passes on the WIN-TRACK Gait Analysis Platform at their self-selected walking speed. The arithmetic mean of the five flawless walking data was used for analysis. Pain intensity is assessed by the Visual Analog Scale (VAS). RESULTS: The spatiotemporal gait parameters were significantly decreased in LDH and CMLBP groups than the healthy control group, particularly in LDH groups (p >= 0.001). It was found that pain intensity is negatively correlated to step and stride length, cadence and velocity (p<0.001). Results of linear regression analysis showed that 10% of the changes in gait cycle duration of the left extremity and 74% of the changes in the velocity were associated with pain intensity. CONCLUSION: Pain intensity can affect the spatiotemporal gait parameters in patients with Low Back Pain (LBP). Rehabilitation programs with gait optimization should be considered in the management of patients with LDH and CMLBP.
Keywords: Lumbar disc herniation; Chronic mechanical low back pain; Spatiotemporal gait parameters; Pain; Gait analysis; WALKING; VARIABILITY; VALIDITY; RELIABILITY; DISABILITY; PEOPLE